Alpha Thalassemia/Intellectual Disability X-Linked Deficiency Sensitizes Non-Small Cell Lung Cancer to Immune Checkpoint Inhibitors - Hou, Tao; Jiang, Shun; Wang, Yapeng; Xie, Yangchun; Zhang, Haixia; Feng, Yeqian; Ma, Fang; Ma, Jin’an; Liu, Xianling; Hu, Chunhong (Frontiers in Oncology, 2020)
Background: The immune checkpoint inhibitors (ICIs) have achieved great success in the treatment of non-small cell lung cancer (NSCLC) patients. However, the response rate is low. The molecular mechanism involved in the effectiveness of ICIs remains to be elucidated. Methods: ATRX mutation incidence among human cancers were analyzed from TCGA database. Atrx deficient lewis lung cancer cell line (LLC-sgAtrx) was established via AAV-CRISPR. Subcutaneous and metastasis models were established by subcutaneous and intravenous injection of LLC-sgAtrx and LLC-sgNTC cells into female C57BL/6 mice. The mice were treated with anti-PD1, anti-CLTA4 or Rat IgG2a. Tumor volume was determined by Vernier calipers and the IVIS imaging system. The proportions of CD3+ T cells, CD45+ immune cells, and the expression of pMHC I and PDL1 were determined by flow cytometry. The T cell cytotoxicity was determined by co-culture experiment. Results: TCGA data showed that Atrx is a tumor suppressor mutated at high frequency among various human cancers. The tumor volume of mice bearing LLC-sgAtrx was significantly shrinked and the median survival of mice was significantly longer after anti-PD1 and anti-CTLA4 treatment. Flowcytometry results showed that Atrx deficiency increase the penetration of CD3+ T cell into the tumor microenvironment and enhanced antigen presentation after IFNγ stimulation. Additionally, the tumor cells with Atrx deficiency were more easily to be damaged by T cells under IFNγ stimulation. Conclusion: The present study demonstrated that Atrx deficiency sensitize lung cancer cells to ICIs by multiple mechanisms. And ATRX may serve as a promising biomarker for ICIs which helps patient stratification and decision making.